Conditions for the onset of the current filamentation instability in the laboratory. (10th May 2018) - Shukla, N.; Vieira, J.; Muggli, P.; Sarri, G.; Fonseca, R.; Silva, L. O.
Abstract : The current filamentation instability (CFI) is capable of generating strong magnetic fields relevant to the explanation of radiation processes in astrophysical objects and leads to the onset of particle acceleration in collisionless shocks. Probing such extreme scenarios in the laboratory is still an open challenge. In this work, we investigate the possibility of using neutral e^- e^+ beams to explore the CFI with realistic parameters, by performing two-dimensional particle-in-cell simulations. We show that CFI can occur unless the rate at which the beam expands due to finite beam emittance is larger than the CFI growth rate and as long as the role of the competing electrostatic two-stream instability (TSI) is negligible. We also show that the longitudinal energy spread, typical of plasma-based accelerated electron–positron fireball beams, plays a minor role in the growth of CFI in these scenarios.